Factors influencing organization commitment at Petronas Carigali Sdn Bhd / Norhidayah Abdul Ghafar and Nur Darina Abd Gani - Abdul Ghafar, Norhidayah; Abd Gani, Nur Darina (Faculty of Business and Management, 2014)
This thesis presents a study, which has sought the most influence factors that affect organization commitment at PETRONAS Carigali Sdn Bhd. So, in this study, researchers will be describing the aspects that influence the organization commitment, which is job satisfaction, perceived organization support, and person organization fit, as well as how they can be related to each other. This report also has highlighted several issues, and their implication of organization commitment. A survey was conducted through distribution of questionnaire to the employees from different background profile of PETRONAS Carigali Sdn Bhd. Researchers was distributed 70 sets of questionnaires to the respondents at PETRONAS Carigali Sdn Bhd. The results from the data were analyzed by using SPSS computer software. An overview of descriptive values of all analysis variables such as frequencies and percentages for main characteristics of the sample was given. Data was obtained and subjected to the reliability of the scales was confirmed by calculating Cronbach’s Alpha for each scale used in the study. From the findings, the researcher also gives some recommendations for the organization and future researcher.